Optimal duration of dual antiplatelet therapy after drug-eluting stent implantation: conceptual evolution based on emerging evidence - Palmerini, Tullio; Stone, Gregg W (European heart journal, 2016)
The objective of this article is to review the contemporary literature on optimal dual antiplatelet therapy (DAPT) duration after drug-eluting stent (DES) implantation. Relevant studies were searched through MEDLINE, the Cochrane database, and the EMBASE database. Of the 6852 publications retrieved, 23 were considered relevant, including 11 randomized controlled trials (RCTs) and 12 meta-analyses. Initially prescribed for 3-6 months after first-generation DES, the recommended duration of DAPT was subsequently prolonged to at least 1 year, a response to reports of late stent thrombosis after DAPT discontinuation. Seven RCTs subsequently suggested that 1-year DAPT may not be necessary after DES implantation, and that a 6-month or even a 3-month course of DAPT may be as effective and safer. In contrast, four RCTs examining the benefit of DAPT beyond 1 year reached conflicting conclusions. In the DAPT trial, 30-month compared with 12-month DAPT after DES resulted in reduced rates of stent thrombosis and major adverse cardiovascular events, but greater rates of major bleeding with increased non-cardiac mortality. Several meta-analyses have subsequently been performed collectively demonstrating increased rates of all-cause mortality with prolonged DAPT compared with shorter DAPT after DES, due to greater non-cardiovascular mortality with prolonged DAPT not offset by a concomitant reduction in cardiac mortality. The benefit-risk ratio of prolonged DAPT appears to be better in patients with myocardial infarction (MI) than in those without prior MI. On the basis of these findings, a personalized approach is advisable when deciding upon the optimal duration of DAPT after DES, wherein the individualized risks of ischaemic vs. bleeding events are carefully considered for each patient.